Effects of dietary Lactobacillus reuteri and Pediococcus acidilactici on the cultured water qualities, the growth and non-specific immune responses of Penaeus vannamei. Issue 127 (August 2022) - Wu, Yu-Sheng; Chu, Yu-Ting; Chen, Yin-Yu; Chang, Chao-Sheng; Lee, Bao-Hong; Nan, Fan-Hua
Abstract: This study discussed the effects of two types of lactic acid bacteria, Lactobacillus reuteri ( L. reuteri ) and Pediococcus acidilactici ( P. acidilactici ), on the growth and nonspecific immunity of Penaeus vannamei ( P. vannamei ) and developed probiotic applications for shrimp cultivation. This study incorporated two types of lactic acid bacteria in shrimp feed through spraying. The shrimps were grouped according to the type and concentration of effective bacteria incorporated into their feed. This research was separated into 3 individual feeding treatment as control, L. reuteri (Lr groups) and P. acidilactici (Pa groups). The shrimp was feeding with 10 3, 10 5, and 10 7  cfu/feed (g) L. reuteri namely as Lr3, Lr5, and Lr7. The shrimp was feeding with 10 3, 10 5, and 10 7  cfu/feed (g) P. acidilactici were named Pa3, Pa5, and Pa7, respectively. Through 8 weeks of feeding, the results revealed that the use of shrimp feed incorporated with lactic acid bacteria did not cause negative effects on water quality. The testing items include ammonia-nitrogen concentration, nitrite-nitrogen concentration, and total vibrio count in the water. In addition, the lactic acid bacteria concentration in the water were in the range of 1.33 ± 0.58 × 10 1 to 9.77 ± 1.34 × 10 2  cfu/mL. Observations of the growth performance of the white shrimps after 8 weeks of feeding revealed that both bacteria were beneficial to shrimp growth. In particular, group Lr7 had the highest percentage weight gain (107.99 ± 3.92%), special growth rate (1.93 ± 0.07%), feed conversion ratio (3.34 ± 0.05), and survival rate (97.22 ± 4.81%). Furthermore, observations of the nonspecific immunity reactions of the white shrimps after 4 weeks of feeding indicated that on day 4, the total number of haemocyte in shrimps in groups Lr5, Lr7, Pa3, and Pa5 significantly increased. On days 1 and 4, the phenoloxidase activity and superoxide axion production rates of the Lr group and Ls group increased. This phenomenon was the most significant in group Lr7, and the effect continued until day 28. After day 7, the phagocytic rate of groups Lr5 and Lr7 significantly increased. In addition, Lr and Pa groups exhibited significant increases in the phagocytic index after days 4 and 14, respectively. This phenomenon was also the most significant in group Lr7. Highlights: Lactobacillus reuteri and Pediococcus acidilactici significantly improved white shrimp growth effect. Higher concentrations of Lactobacillus reuteri and Pediococcus acidilactici significantly improved nonspecific immunity. Lactobacillus reuteri and Pediococcus acidilactici can serve as a feed additive with development potential.